Interpretasi Rekahan Hydraulic Fracturing dengan Menggunakan Permodelan Simulator Fraccade Berdasarkan hasil Rock Properties Pada Sumur X Lapangan Y - Nugroho Marsiyanto; Edy Soesanto; Eko Prastio; Aulia Ismanto (Jurnal Bhara Petro Energi, 2023)
Interpretation Fractures of Hydraulic fracturing with Fraccade Model Based on Rock Properties Results at Well X Field Y.Identifying fractures based on the results of Rock Properties purpose is to find out and get results during the identification process from the results of Hydraulic fracturing stimulation with the purpose of getting a conclusionwhether or not the operation is successful. Well X has several problems such as high skin and low permeability, because of that Hydraulic fracturing stimulation is the most effective action for this well.The method used is to select data data and the condition of well X to visualize the data results from Fraccade software V 5.4.1. And do calculations using Ms. Excel. The parameters that calculated in this Final Project include rock geometry, rock permeability, and wellbore damage. After identifying and interpreting the data using Fraccade V 5.4.1 software. The results show that not much different between manual calculation and Fraccade software.